1994
DOI: 10.1210/jcem.78.2.8106628
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary iodine intake and prevalence of subclinical hypothyroidism in the coastal regions of Japan.

Abstract: The prevalence of thyroid dysfunction in relation to iodine intake was studied in adults (n = 1061) in five coastal areas of Japan that produce iodine-rich seaweed (kelp). The prevalence of hyperthyroidism (TSH < 0.15 mU/L) was similar in these areas, whereas that of hypothyroidism (TSH > 5.0 mU/L) varied from 0-9.7%. The relative frequency of above normal iodide concentration in the morning urine (> or = 75 mumol/L) [high urinary iodide (UI)] varied from 3.7%-30.3%. Together with previously reported results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 22 publications
4
46
4
Order By: Relevance
“…), topical antiseptics, and contrast dyes. In addition to the epidemiologic evidence, dinical studies have suggested a relationship of elevated iodine intake in autoimmune thyroid diseases (16)(17)(18)(19). The effects of high iodine uptake, however, are observed only in genetically susceptible individuals (20).…”
Section: Iodine As An Environmental Trigger Of Autoimmune Thyroiditismentioning
confidence: 99%
“…), topical antiseptics, and contrast dyes. In addition to the epidemiologic evidence, dinical studies have suggested a relationship of elevated iodine intake in autoimmune thyroid diseases (16)(17)(18)(19). The effects of high iodine uptake, however, are observed only in genetically susceptible individuals (20).…”
Section: Iodine As An Environmental Trigger Of Autoimmune Thyroiditismentioning
confidence: 99%
“…Zava and Zava 7 estimated that Japanese iodine intake, which comes largely from seaweed consumption, ranges from 1 to 3 mg/day. The mean or median UIC of Japanese residents ranges from 281 to 3300 μg/L in many regions of Japan 8, 9, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…A few people developed goiters at this intake level (39>43). Those who ingested 3-16 mg/day iodine had a 10% incidence of goiter, but clinical hypothyroidism in this population was rare (43,44 clinically euthyroid. Assuming they ingested an average of 2 L water/day, this is the lowest documented iodine dose to produce goiter, even accounting for the lower body weight of the children.…”
Section: Thyroid Effects Of Excess Iodine Ingestionmentioning
confidence: 71%
“…Clinical hypothyroidism is rare among Japanese with endemic goiter due to long-term ingestion of excess iodine. In these cases, both thyroid function and thyroid size return to normal when excess iodine consumption is stopped, unless underlying thyroid disease is present (36,38,39,43).…”
Section: Thyroid Effects Of Excess Iodine Ingestionmentioning
confidence: 99%